You gotta walk the walk to talk the talk: protocol for a feasibility study of the Happy Older Latino Adults (HOLA) health promotion intervention for older HIV-positive Latino men - Daniel E. Jimenez; Elliott R. Weinstein; John Batsis (Pilot and Feasibility Studies, 2023)
Abstract Background Older Latinos living with the human immunodeficiency virus (HIV) have been disproportionately affected by the epidemic and experience compounded health disparities that have deepened over time. These health disparities are largely related to lifestyle and are either preventable or amenable to early detection or intervention. Despite existing resources to deliver an intervention to reduce this compounded health disparity, there is little information on the effects of health promotion interventions on indices of cardiometabolic risk in midlife and older Latinos living with HIV. The Happy Older Latinos are Active (HOLA) intervention is an innovative health promotion program that is uniquely tailored to meet the diverse needs and circumstances of older Latinos with HIV. The goal of this manuscript is to describe the protocol of a feasibility study of the HOLA health promotion intervention for older HIV-positive Latino men. Methods/design HOLA, which is informed by Behavioral Activation and Social Learning theory is a community health worker (CHW)-led, multicomponent, health promotion intervention consisting of: (1) a social and physical activation session; (2) a moderately intense group walk led by a CHW for 45 min, 3×/week for 16 weeks; (3) pleasant events (e.g., going to brunch with friends) scheduling. Eighteen community dwelling Latinos living with HIV aged 50+ will be recruited for this feasibility study adapting the HOLA intervention. Participants will be assessed at three time points (baseline, post-intervention, and 3 months post-intervention) on measures of cardiometabolic risk factors (waist circumference, dyslipidemia, hypertension, and glucose), psychosocial functioning, and health-related quality of life. Conclusions If HOLA can be delivered successfully by CHWs, then the scalability, accessibility, and potential for dissemination is increased. Additionally, this study will inform feasibility and identify modifications needed in the design of a larger hypothesis testing study. Trial registration Clinicaltrials.gov Identifier: NCT 03839212. Date of Registration: 8 February, 2019.